1993
DOI: 10.1557/jmr.1993.0899
|View full text |Cite
|
Sign up to set email alerts
|

Processing of electroceramic-polymer composites using the electrorheological effect

Abstract: This paper presents a novel approach that demonstrates the usefulness of electrorheological fibril formation to form f-3 connected ceramic-polymer composites. These fillers include ferroelectric, polar, metal, semiconductor, and superconductor crystallite powders. Patterned distributions of ceramic fillers within the polymer matrix can be induced by electric fields applied between patterned electrodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…[9][10][11][12][13][14][15] It is demonstrated that dielectrophoresis can be used for structuring of PZT particles as columns in a polymer matrix, resulting in composites with quasi 1-3 connectivity. [16][17][18][19] This will keep the manufacturing process as simple as 0-3 composites, and consequently, production costs can be kept low. In dielectrophoresis, when a moderate electric field is applied across a suspension of ferroelectric particles in an insulating medium, the particles orient themselves toward the direction of applied electric field.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15] It is demonstrated that dielectrophoresis can be used for structuring of PZT particles as columns in a polymer matrix, resulting in composites with quasi 1-3 connectivity. [16][17][18][19] This will keep the manufacturing process as simple as 0-3 composites, and consequently, production costs can be kept low. In dielectrophoresis, when a moderate electric field is applied across a suspension of ferroelectric particles in an insulating medium, the particles orient themselves toward the direction of applied electric field.…”
Section: Introductionmentioning
confidence: 99%
“…Electric fields have also been used to make oriented structures in other polymer systems including one- 10,11 and two-phase 12,13 polymer solutions, block copolymer melts, [14][15][16][17] homopolymer/block copolymer mixtures, 18 and polymer/ceramic composites. 19,20 Morphology development in polymer mixtures containing two immiscible homopolymers dissolved in a mutual solvent in the presence of a dc electric field during solvent evaporation was first investigated by Venugopal et al [3][4][5] The polymer mixtures used included polystyrene (PS) with such other polymers as poly(ethylene oxide) (PEO), poly(methyl methacrylate) (PMMA), poly(vinyl acetate) (PVA), polybutadiene (PB), and poly(vinyl chloride) (PVC) in toluene or cyclohexanone as a solvent. They showed that when the dielectric constants of the dispersed phase ( d ) and the matrix ( m ) were about the same, namely, in the PS/ PB/toluene system, there was no apparent droplet deformation.…”
Section: Introductionmentioning
confidence: 99%
“…Orientation of this filler in the thickness direction will decrease the spacing between silica particles and intensify the dipolar interaction between polarized particles in this direction. Less the spacing between particles, higher the intensity of local electric fields, and thus higher dielectric permittivity would be [17]. Orientation of filler particles in the thickness direction has not increased dielectric loss of the composite significantly, as shown in Figure 5.…”
Section: Dielectric Behavior Of Compositesmentioning
confidence: 94%